Integrasi Pendekatan STEM dalam Pengembangan Modul Materi Fungsi - Syailla Afifah; Kristayulita Kristayulita; Parhaini Andriani (Universitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to develop a STEM-based mathematics learning module on linear functions that meets the criteria of validity, practicality, and effectiveness. The purpose of the module development is to improve the efficiency and effectiveness of learning in schools in terms of time, cost, facilities, and human resources. The research method used is Research and Development (R&D) with the ADDIE development model. The trial was conducted at an MTsN, involving 6 students in a small group trial, 20 eighth-grade students in a field test, and 1 teacher. Validation was carried out by a subject matter expert and a media expert. The research instruments included validation sheets, response questionnaires, and tests. The validation results indicated a very high level of validity, the practicality was categorized as practical to very practical, and the effectiveness of the module was shown by an N-Gain score of 0.91 (high category). This module differs from conventional ones by fully integrating the STEM approach and presenting linear function material in an interactive and applicable context. Its strengths lie in its flexibility as self-instructional material, ease of use for teachers, and its ability to enhance learning effectiveness.Abstrak: Penelitian ini bertujuan mengembangkan modul pembelajaran matematika berbasis STEM pada materi fungsi linear yang memenuhi kriteria valid, praktis, dan efektif. Modul ini dikembangkan untuk meningkatkan pemahaman konsep fungsi dan keterampilan berpikir kritis siswa melalui pembelajaran yang kontekstual dan interdisipliner. Keunggulan modul ini terletak pada penerapan pendekatan STEM yang terintegrasi dengan penyajian materi fungsi linear dalam bentuk yang aplikatif, interaktif, dan relevan dengan kehidupan nyata. Keunggulannya terletak pada fleksibilitas sebagai bahan ajar mandiri, kemudahan bagi guru, dan peningkatan efektivitas pembelajaran. Metode penelitian yang digunakan adalah Research and Development (R&D) dengan model ADDIE. Uji coba dilakukan di MTsN dengan melibatkan 6 siswa (kelompok kecil), 20 siswa kelas VIII (uji lapangan), dan 1 guru. Validasi dilakukan oleh ahli materi dan ahli media. Instrumen penelitian berupa lembar validasi, angket respons, dan tes. Hasil validasi menunjukkan tingkat kevalidan sangat tinggi, kepraktisan tergolong praktis hingga sangat praktis, dan efektivitas modul ditunjukkan dengan skor N-gain sebesar 0,91 (kategori tinggi).